Effect of Alcohol on Diffuse Axonal Injury in Rat Brainstem: Diffusion Tensor Imaging and Aquaporin-4 Expression Study. (27th October 2013) - Kong, Lingmei; Lian, Gengpeng; Zheng, Wenbin; Liu, Huimin; Zhang, Haidu; Chen, Ruowei
Abstract : The aim of this study is to assess the effects of alcohol on traumatic brain injury by using diffusion tensor imaging (DTI) and evaluate aquaporin-4(AQP4) expression changes in rat brainstems following acute alcohol intoxication with diffuse axonal injury (DAI). We further investigated the correlation between the AQP4 expression and DTI in the brain edema. Eighty-five rats were imaged before and after injury at various stages. DTI was used to measure brainstem apparent diffusion coefficient (ADC) and fractional anisotropy (FA), with immunostaining being used to determine AQP4 expression. After acute alcoholism with DAI, ADC values of the brainstem first decreased within 6 h and then elevated. FA values began to decline by 1 h, reaching a minimum at 24 h after trauma. There was a negative correlation between ADC values and brainstem AQP4 expression at 6 h and positive correlation at 6 h to 24 h. Changes of ADC and FA values in DAI with acute alcoholism indicate the effects of ethanol on brain edema and the severity of axonal injury. The correlations between ADC values and the brainstem AQP4 expression at different time points suggest that AQP4 expression follows an adaptative profile to the severity of brain edema.